Sejmiks of Minsk and Minsk Citizens Towards the Reforms of the Four-Year Sejm (1788–1792) - Rolnik, Dariusz (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
Citizens of Minsk approached the sejmiks before the 1788 Sejm with the expectation of reforming the whole state. However, they wanted above all the successful development of their small homeland. This can be seen in subsequent sejmiks, where the main attention was paid to the election of officials, mainly deputies. It was only at the assembly in November 1790 that the citizens of Minsk supported the reforms, although they did not agree to the hereditary throne. On this point a change occurred in February 1792. This next assembly approved the Constitution of 3 May. Some of the citizens spoke against it in Minsk at that time. This was verified by the Polish-Russian war in defense of the May Act. Citizens of Minsk supported the reform camp, but they were also aware of the proximity of Russia. Later they acknowledged the advantage of the victors, but not convienced, they clung to their small homeland. Against this background, it is interesting to note the animosities between families forming the elite of the Minsk voivodeship. The bad Ignacy Daszkiewicz and the good Adam Chmara. The question remains open as to what extent the gravity of the situation, the threat of the fall of the Republic, induced the feuding families to reconcile and abandon privatism. However, it should be noted that in the Mińsk voivodeship – which is not an exception – all elite members worked together on important matters important for their small fatherlands, and making personal conflicts became of secondary importance.